Acceptance of Online Study: A Survey On Teachers and Learners in Malaysia - Menaga, Vesudevan; Azureen, Abd Aziz (INTI International University, 2020)
Technology is identified as a fragment of tools in society and technology in education is the groundwork for countries to improve learners’ academic interests at private institutions. The research is to discover the lecturers’ perception of factors Inducing Online Integration in teaching and learning and learners’ interest in the lesson. The purpose of this study is to overview the lecturer’s discernment on the practices of online integration in teaching and learning and the level of learners’ interest in the courses. The enhanced curriculum will be established based on teaching and online. These researches were conducted at private institutions in Negeri Sembilan by using a quantitative research method which is distributing the questionnaire. The total respondent of lecturers of this study is 150 people, who are teaching in private institutions. The survey questionnaire was used as the main tool for data collecting. The findings show a positive impact on the online integration in teaching and learning and learners’ interest in the courses.